2011
DOI: 10.1089/neu.2010.1699
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Low versus High Amounts of Weight Supported Treadmill Training in Spinally Transected Rats

Abstract: Intensive weight-supported treadmill training (WSTT)improves locomotor function following spinal cord injury. Because of a number of factors, undergoing intensive sessions of training may not be feasible. Whether reduced amounts of training are sufficient to enhance spinal plasticity to a level that is necessary for improving function is not known. The focus of the present study was to assess differences in recovery of locomotor function and spinal plasticity as a function of the amount of steps taken during W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
1
29
1
Order By: Relevance
“…2F) and the weak Ib excitation during the stance phase in AIS C and D (Fig. 6, C and F) may depend on the number of training sessions, the number of steps per session (de Leon et al 2011), or even the BWS since loading can affect the net EMG output (Dietz et al 2002). The BWS during training was adjusted separately for each participant based on his/her ability to step without knee buckling or toe dragging, and thus quantification of BWS effects is not possible.…”
Section: Discussionmentioning
confidence: 96%
“…2F) and the weak Ib excitation during the stance phase in AIS C and D (Fig. 6, C and F) may depend on the number of training sessions, the number of steps per session (de Leon et al 2011), or even the BWS since loading can affect the net EMG output (Dietz et al 2002). The BWS during training was adjusted separately for each participant based on his/her ability to step without knee buckling or toe dragging, and thus quantification of BWS effects is not possible.…”
Section: Discussionmentioning
confidence: 96%
“…Treadmill training in rodents after SCI is commonly used to investigate the role of repetitive movement training (e.g., spinal learning) with moderate to severe paralysis, or to investigate the contribution of physical exercise on recovery in animals able to walk with weight-supported steps. 16,19,[28][29][30][31][32][33] In the lesion model studied here, 1 week of daily treadmill training beginning 4 weeks post-injury did not significantly reduce footslip errors on the ladder task, nor did AIH administered at the same time as treadmill training improve ladder performance post-treatment (Fig. 5).…”
Section: Involuntary Walking Training Does Not Improve Ladder Performmentioning
confidence: 77%
“…These training parameters were based on our previous studies that showed positive effects of 4–6 weeks of training in SCI rats. 10,11,2023 The robotic device (Rodent Robot 3000, Robomedica Inc., Irvine, California) consisted of a motorized treadmill and a body weight support (BWS) apparatus for control over hindlimb weight bearing (Fig. 1A).…”
Section: Robotic Trainingmentioning
confidence: 99%
“…10,11,2023 All rats were tested for their ability to step without any resistive forces and at a treadmill speed of 10 cm·s −1 . The duration of testing was typically 1 minute as a precaution against any training effects, especially in the UT group.…”
Section: Locomotor Testsmentioning
confidence: 99%